A new Volterra series based orthogonal behavioral model for power amplifiers - Lavrador, P.M.
In this paper a new Volterra Series based behavioral model for active nonlinear RF power amplifiers is presented. The proposed model's main advantage is the possibility of extraction of it's parameters orthogonally. Some validation results are presented both in the time and frequency domains, using an IS-95 CDMA signal. © 2005 IEEE.